Assessment of physiological characteristics of Paulownia hybrid exposed to different water regimes - Maskin, Alyani Izzareena (2018)
Paulownia is a genus belonging to family Paulowniaceae which is indigenous to China. It is known as a fast growing species and had been introduced to be planted in Malaysia. However, there is a lack of information about the plasticity of the species to adapt with the environment when planted in Malaysia as the country is well known for having different precipitation in diverse zone. Therefore, this study was conducted to examine the physiological characteristics and water use efficiency of the species by exposed them to three different water regimes, which were low, medium and high. The results showed that the plant that was exposed to a high water regime had greater net photosynthesis (16.425 molm⁻²s⁻¹), stomata conductance (0.579 mol H₂O m⁻²s⁻¹), intercellular CO₂ (365.817 mol CO₂m⁻²s⁻¹) and transpiration rate (3.931 mmol H₂O m⁻²s⁻¹) than the plant that was exposed to the low and medium water regimes. However, the plant that was exposed to the high water regime also had the lowest values for the leaf to air vapour deficit in leaf (0.950 D), intrinsic water use efficiency (37.834 mol CO₂mol H₂O) and instantaneous water use efficiency (4.430 mol CO₂mol H₂O). Measurements of the gas exchange are useful for the detection of the effects of water regimes that exposed to the Paulownia hybrid. Different levels of water regimes were significantly affecting the physiological characteristic of the Paulownia hybrid.